2016
DOI: 10.3747/pdi.2014.00123
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Decline of Residual Renal Function in Children Treated with Peritoneal Dialysis

Abstract: ♦ BACKGROUND: The aim of the study was to assess risk factors for residual renal function (RRF) decline in children during the first/second year of chronic peritoneal dialysis (PD). ♦ METHODS: The study group included 56 children with end-stage renal disease (ESRD) (age 10.13 ± 4.86 years), including 18 on continuous ambulatory PD (CAPD) and 38 on automated PD (APD), in whom we evaluated RRF (daily diuresis [mL/m/24 h], residual glomerular filtration rate (rGFR) [mL/min/1.73 m]), etiology of ESRD, PD fluid vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…Studies of adult patients undergoing peritoneal dialysis suggested that hypertension, especially systolic hypertension, was an important risk factor for rapid loss of RRF: compared with patients with normal systolic blood pressure, patients with higher systolic blood pressure levels had a faster rate of residual urine decline in the first year, which was one of the independent risk factors leading to RRF loss. 15,18 The data in this study showed that the oligoanuria group had higher initial systolic and diastolic blood pressure levels; however, multivariate analysis could not sufficiently confirm that these parameters were independent risk factors for RRF loss in children receiving APD treatment. Previous studies have also suggested that antihypertensive drug use was an important risk factor for RRF loss.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Studies of adult patients undergoing peritoneal dialysis suggested that hypertension, especially systolic hypertension, was an important risk factor for rapid loss of RRF: compared with patients with normal systolic blood pressure, patients with higher systolic blood pressure levels had a faster rate of residual urine decline in the first year, which was one of the independent risk factors leading to RRF loss. 15,18 The data in this study showed that the oligoanuria group had higher initial systolic and diastolic blood pressure levels; however, multivariate analysis could not sufficiently confirm that these parameters were independent risk factors for RRF loss in children receiving APD treatment. Previous studies have also suggested that antihypertensive drug use was an important risk factor for RRF loss.…”
Section: Discussioncontrasting
confidence: 62%
“…The mean glucose loading in this study was quite higher than reported in the other study (101.51 g/m 2 /day vs. 52.40 g/m 2 /day). 15 This might be due to the lower initial urine volume in our cohort (659.77ml/m 2 /day vs. 1394.93 ml/m 2 /day), 15 which has been reported that different regions have various residual urine output. 7 This observed associations of higher glucose loading and daily ultrafiltration volume with a higher risk of RRF loss may reflect the efforts for enhanced dialytic fluid removal in patients with failing RRF.…”
Section: Discussionmentioning
confidence: 73%
“…Similar to previous studies [12, 13, 31–33], we found that high baseline RRF was the major predictor of the fast decline of RRF in the first year. A possible explanation for this might be that RRF was found to decline exponentially after the onset of therapy [3].…”
Section: Discussionsupporting
confidence: 91%
“…Hypertension is highly prevalent in HFpEF and plays a critical role in its etiology because hypertension contributes to left ventricular hypertrophy, diastolic dysfunction, abnormal ventricular arterial coupling, and even end-organ damage [30]. Preservation of residual renal function is critical for survival in adults with end-stage renal disease receiving chronic PD [31]. After treatment, the levels of SBP, DBP, and 24-h UV of all patients were reduced, and the blood pressure level of patients treated with SAC/VAL was more significantly declined than that of the controls.…”
Section: Discussionmentioning
confidence: 99%